Morphological and molecular analysis of cryptic native and invasive freshwater snails in Chile - Collado, Gonzalo A. (2019)
Species delimitation in minute freshwater snails is often difcult to perform using solely shell morphology. The problem intensifes when invasive species spread within the distribution range of morphologically similar native species. In Chile, the Truncatelloidean snails are represented by the native genera Heleobia and Potamolithus plus the invasive mudsnail Potamopyrgus antipodarum, which can easily be confused. Using an integrative approach, we performed molecular phylogenetic analysis and studied reproductive and morphological features to identify superfcially similar forms inhabiting the central area of the country. Truncatelloidean snails were identifed in 40 of 51 localities sampled, 10 containing Potamopyrgus antipodarum, 23 Heleobia and 7 Potamolithus. Based on these results and previously published data, the known distribution of the mudsnail in Chile encompasses 6 hydrological basins, including 18 freshwater ecosystems. The fnding of the mudsnails in several type localities of native species/subspecies of “Heleobia” that were not fnd in situ suggests species replacement or signifcant extinction of native fauna, a hypothesis supported by the restudy of type material that shows that endemic forms belong to the genus Potamolithus. This study shows the usefulness of integrative taxonomy not only resolving complex taxa with cryptic morphology but also measuring the extent of an ongoing invasion.